The Binding Power of Constitutional Court Decisions Based on Law Number 8 of 2011 Concerning Amendments to Law Number 24 of 2003 - Khairul Umam; Ida Surya; Rusnan Rusnan; Kaharuddin Kaharuddin (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2026)
This study examines the final and binding nature of Constitutional Court decisions under Law Number 8 of 2011 concerning Amendments to Law Number 24 of 2003 on the Constitutional Court, with particular emphasis on the relationship between constitutional finality, legal certainty, and justice. This study employs normative legal research using statutory and conceptual approaches. Legal materials are analyzed through statutory and authentic interpretation, complemented by philosophical analysis of constitutional adjudication. The findings demonstrate that Constitutional Court decisions acquire permanent legal force immediately upon their pronouncement and are not subject to appeal or other ordinary legal remedies. Their finality also establishes binding force beyond the litigating parties, reflecting the Constitutional Court’s position as the guardian and authoritative interpreter of the Constitution. Although such finality may raise concerns regarding potential judicial errors and access to corrective remedies, it remains constitutionally justified by the supremacy of the Constitution, the institutional position of the Constitutional Court as a court of first and final instance, and the need to ensure legal certainty in constitutional disputes. Therefore, the final and binding character of Constitutional Court decisions constitutes an essential mechanism for maintaining constitutional authority, legal certainty, and stability within Indonesia’s constitutional system.